Entry of Francisella tularensis into Murine B Cells: The Role of B Cell Receptors and Complement Receptors - Plzakova, Lenka; Krocova, Zuzana; Kubelkova, Klara; Macela, Ales (PloS one, 2015)
Francisella tularensis, the etiological agent of tularemia, is an intracellular pathogen that dominantly infects and proliferates inside phagocytic cells but can be seen also in non-phagocytic cells, including B cells. Although protective immunity is known to be almost exclusively associated with the type 1 pathway of cellular immunity, a significant role of B cells in immune responses already has been demonstrated. Whether their role is associated with antibody-dependent or antibody-independent B cell functions is not yet fully understood. The character of early events during B cell-pathogen interaction may determine the type of B cell response regulating the induction of adaptive immunity. We used fluorescence microscopy and flow cytometry to identify the basic requirements for the entry of F. tularensis into B cells within in vivo and in vitro infection models. Here, we present data showing that Francisella tularensis subsp. holarctica strain LVS significantly infects individual subsets of murine peritoneal B cells early after infection. Depending on a given B cell subset, uptake of Francisella into B cells is mediated by B cell receptors (BCRs) with or without complement receptor CR1/2. However, F. tularensis strain FSC200 ΔiglC and ΔftdsbA deletion mutants are defective in the ability to enter B cells. Once internalized into B cells, F. tularensis LVS intracellular trafficking occurs along the endosomal pathway, albeit without significant multiplication. The results strongly suggest that BCRs alone within the B-1a subset can ensure the internalization process while the BCRs on B-1b and B-2 cells need co-signaling from the co receptor containing CR1/2 to initiate F. tularensis engulfment. In this case, fluidity of the surface cell membrane is a prerequisite for the bacteria's internalization. The results substantially underline the functional heterogeneity of B cell subsets in relation to F. tularensis.
Keywords: Membrane Microdomains; receptory antigenů B-buněk; Receptors, IgG; Animals; mikrobiální viabilita; membránové mikrodomény; tularemie; Microbial Viability; Mice, Inbred BALB C; B-lymfocyty; Genes, Bacterial; bakteriální geny; receptory IgG; Female; Receptors, Complement; Sequence Deletion; Host-Pathogen Interactions; buněčné linie; ženské pohlaví; Cell Line; myši inbrední BALB C; zvířata; B-Lymphocytes; receptory komplementu; Tularemia; Biological Transport; sekvenční delece; Francisella tularensis; biologický transport; Receptors, Antigen, B-Cell; interakce hostitele a patogenu